The immune dysregulations in COVID-19: Implications for the management of rheumatic diseases. Issue 5 (3rd September 2021) - Xiao, Fan; Han, Man; Zhu, Xiaoxia; Tang, Yuan; Huang, Enyu; Zou, Hejian; Jiang, Quan; Lu, Liwei
Abstract: The pandemic of COVID-19 has caused global social impact and high health risk. Clinical observations have suggested that elevated levels of inflammatory mediators are associated with disease severities in COVID-19 patients, in which the immunological profiles indicate the hyperactivation of innate immune cells and dysregulated adaptive immune responses. The increasing prevalence and disease progression of COVID-19 has emerged as a pressing challenge for the management of rheumatic patients with immune dysregulations. Here we review the immune dysregulations in COVID-19 and discuss the management of COVID-19 patients with rheumatic diseases.